Sex, gender, and the sacred : reconfiguring religion in gender history - De Groot, Joanna, 1947- (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2014)
Sex, Gender and the Sacred presents a multi-faith, multi-disciplinary collection of essays that explore the interlocking narratives of religion and gender encompassing 4,000 years of history. Contains readings relating to sex and religion that encompass 4,000 years of gender historyFeatures new research in religion and gender across diverse cultures, periods, and religious traditions. Presents multi-faith and multi-disciplinary perspectives with significant comparative potentialOffers original theories and concepts relating to gender, religion.
Introduction: Beyond the'Religious Turn'? Past, Present and Future Perspectives in Gender History / Joanna de Groot, Sue Morgan -- Crossing Cultures and Transnational Exchanges. Witches, Female Priests and Sacred Manoeuvres: (De)Stabilising Gender and Sexuality in a Cuban Religion of African Origin / Carolyn E Watson -- Liberal Religion and the'Woman Question' between East and West: Perspectives from a Nineteenth-Century Bengali Women's Journal / Clare Midgley -- Indeterminacy in Meaning: Religious Syncretism and Dynastic Historiography in the / Yuet Keung Lo --'All of Their Customs are Daughters of Their Religion': Baptists in Post-Revolutionary Mexico, 1920s-present / Kathleen M McIntyre -- Creating the'Problem Hindu': Sati, Thuggee and Female Infanticide in India, 1800-60 / Daniel J R Grey -- Religion, Embodiment and Subjectivity. Engendering Purity and Impurity in Assyriological Studies: A Historiographical Overview / Erica Couto-Ferreira, Agnès Garcia-Ventura -- Lamentation Motifs in Medieval Hagiography / Anne E Bailey -- Architecture of Desire: Mediating the Female Gaze in the Medieval English Anchorhold / Michelle M Sauer -- The Alluring Beauty of a Leonardesque Ideal: Masculinity and Spirituality in Renaissance Milan / Maya Corry --'Deaf to the Word': Gender, Deafness and Protestantism in Nineteenth-Century Britain and Ireland / Esme Cleall -- Religion, Gender and Sexuality. The Sexual Shame of the Chaste:'Abortion Miracles' in Early Medieval Saints' Lives / Zubin Mistry --'Give Me Chastity': Masculinity and Attitudes to Chastity and Celibacy in the Middle Ages / Pat Cullum -- Common Soldiers, Same-Sex Love and Religion in the Early Eighteenth-Century British Army / Susan Gane --'Dark Ecstasies': Sex, Mysticism and Psychology in Early Twentieth-Century England / Joy Dixon -- Made Flesh? Gender and Doctrine in Religious Violence in Twentieth-Century Spain / Mary Vincent -- Gender, Religion and Political Activity. Conversion Trouble: The Alawis of Hadhramawt, Empire, Gender and the Problem of Sovereignty in Nineteenth-Century South India / Wilson Chacko Jacob --'': Exploring the History of a Slogan in Greece, 1880-1930 / Effi Gazi -- The More Things Change: Debating Gender and Religion in India's Hindu Laws, 1920-2006 / Rina Verma Williams.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Sex role -- Religious aspects; Gender identity -- Religious aspects; Sex -- Religious aspects; Sex role -- Religious aspects; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Sex role -- Religious aspects; Electronic books; Electronic books